1997
DOI: 10.1007/bf00115293
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of the mixtures of 4-chlorophenol and phenol by Comamonas testosteroni CPW301

Abstract: A 4-chlorophenol (4-CP)-degrading bacterium, strain CPW301, was isolated from soil and identified as Comamonas testosteroni. This strain dechlorinated and degraded 4-CP via a meta-cleavage pathway. CPW301 could also utilize phenol as a carbon and energy source without the accumulation of any metabolites via the same meta-cleavage pathway. When phenol was added as an additional substrate, CPW301 could degrade 4-CP and phenol simultaneously. The addition of phenol greatly accelerated the degradation of 4-CP due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 24 publications
1
37
1
Order By: Relevance
“…These results suggest that an ortho cleavage pathway may be present in this strain. Contrary to our results, Bae et al (1996) and Liu et al (2002) found that the degradation of aniline goes through meta cleavage; also, Mulla et al (2011) found that Micrococcus sp. strain SMN-1 degraded 2-nitrotoluene through 3-methylcatechol by a meta-cleavage pathway, with release of nitrite.…”
Section: Ring Cleavage Enzymecontrasting
confidence: 99%
“…These results suggest that an ortho cleavage pathway may be present in this strain. Contrary to our results, Bae et al (1996) and Liu et al (2002) found that the degradation of aniline goes through meta cleavage; also, Mulla et al (2011) found that Micrococcus sp. strain SMN-1 degraded 2-nitrotoluene through 3-methylcatechol by a meta-cleavage pathway, with release of nitrite.…”
Section: Ring Cleavage Enzymecontrasting
confidence: 99%
“…Utilization of aromatic compounds as sole carbon sources was determined by using a minimum salt medium (Bae et al, 1996) T to use aromatic compounds in liquid medium with the same components without Noble agar. To minimize evaporation of phenolic compounds, these tests were performed in 160 ml serum bottles with butyl robber stoppers.…”
Section: Nocardioides Marinus Cl-dd14 T (Dq401093)mentioning
confidence: 99%
“…were added separately. The change of aromatic compounds in liquid medium was detected as described previously (Bae et al, 1996).…”
Section: Nocardioides Marinus Cl-dd14 T (Dq401093)mentioning
confidence: 99%
“…Table 2 shows the effect of the phenol addition on the kinetics of PNP degradation. The rapid degradation of PNP in the presence of phenol seemed to be due to the increased cell mass rather than to the enhancement of the specific PNP degrading activity (Bae et al, 1996b). On the other hand, Schmidt et al (1987) reported that phenol had an inhibitory effect on the kinetics of PNP mineralization by Pseudomonas sp.…”
Section: Simultaneous Degradation Of Phenol and Pnpmentioning
confidence: 98%
“…However, chloro-and methylaromatic compounds were simultaneously degraded via the same initial degradation pathway with the conversion to the corresponding substituted catechols (Pettigrew et al, 1991;Rojo et al, 1987;Taeger et al, 1988). Bae et al (1996b) also reported that the mixture of 4-chlorophenol and phenol was degraded via the meta-cleavage pathways of 4-chlorocatechol and catechol, respectively.…”
Section: Simultaneous Degradation Of Phenol and Pnpmentioning
confidence: 99%